2019
DOI: 10.3390/jcm8040422
|View full text |Cite
|
Sign up to set email alerts
|

“With Every Step, We Grow Stronger”: The Cardiometabolic Benefits of an Indigenous-Led and Community-Based Healthy Lifestyle Intervention

Abstract: Community-based and Indigenous-led health and wellness approaches have been widely advocated for Indigenous peoples. However, remarkably few Indigenous designed and led interventions exist within the field. The purpose of this study was to evaluate an Indigenous-led and community-based health and wellness intervention in a remote and rural Indigenous community. This protocol was designed by and for Indigenous peoples based on the aspirations of the community (established through sharing circles). A total of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
0
20
0
2
Order By: Relevance
“…By making small changes in my activities, I can meet my goal to be happier and healthier. The application of strengths-based approaches has increasingly been used in diverse environments (such as the workplace and clinical settings [45,50,52,54,55]), communities, and populations (e.g., children, Indigenous communities) [48,49,[56][57][58][59]. For instance, Zhang et al [50] in a recent systematic review and meta-analysis of randomized controlled trials, revealed that strengths-based, solution-focused brief therapy in medical settings had a significant effect on health-related psychosocial outcomes (e.g., depression, psychosocial adjustment to illness), with positive indicators for health-related behavioral outcomes (e.g., physical activity, nutrition score).…”
Section: Person-centered Messagingmentioning
confidence: 99%
See 3 more Smart Citations
“…By making small changes in my activities, I can meet my goal to be happier and healthier. The application of strengths-based approaches has increasingly been used in diverse environments (such as the workplace and clinical settings [45,50,52,54,55]), communities, and populations (e.g., children, Indigenous communities) [48,49,[56][57][58][59]. For instance, Zhang et al [50] in a recent systematic review and meta-analysis of randomized controlled trials, revealed that strengths-based, solution-focused brief therapy in medical settings had a significant effect on health-related psychosocial outcomes (e.g., depression, psychosocial adjustment to illness), with positive indicators for health-related behavioral outcomes (e.g., physical activity, nutrition score).…”
Section: Person-centered Messagingmentioning
confidence: 99%
“…Strengths-based approaches to health and wellness have increasingly been used within Indigenous communities throughout the world [48,49,57,58,63]. Indigenous peoples have acknowledged the need to consider health and wellness from a more wholistic perspective (including spiritual, emotional, mental, and physical wellbeing) reflecting a balance of human relationships with the natural and spiritual world, including connections amongst the land, individuals, family, community, and cultural and spiritual practices [63].…”
Section: Person-centered Messagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that study completers improved diet quality through an increased proportion of energy intake from healthy core foods and decreased discretionary foods, and improved self-concept, particularly with regards to the physical appearance and attributes domain. Cardiorespiratory fitness was not significantly improved at follow-up, although mean absolute VO 2 peak increased 5%; a comparable modest increase to previous intervention studies in children [47]. Despite being satisfied with the program, few recruited participants met the attendance goals and the attrition rate was higher than expected.…”
Section: Discussionmentioning
confidence: 49%